The protective role of the microenvironment in hairy cell leukemia treatment: Facts and perspectives - Gargiulo, Ernesto; Giordano, Mirta; Niemann, Carsten U.; Moussay, Etienne; Paggetti, Jérôme; Morande, Pablo Elías (Frontiers in Oncology, 2023)
Hairy cell leukemia (HCL) is an incurable, rare lymphoproliferative hematological malignancy of mature B cells. Although first line therapy with purine analogues leads to positive results, almost half of HCL patients relapse after 5-10 years, and standard treatment may not be an option due to intolerance or refractoriness. Proliferation and survival of HCL cells is regulated by surrounding accessory cells and soluble signals present in the tumor microenvironment, which actively contributes to disease progression. In vitro studies show that different therapeutic approaches tested in HCL impact the tumor microenvironment, and that this milieu offers a protection affecting treatment efficacy. Herein we explore the effects of the tumor microenvironment to different approved and experimental therapeutic options for HCL. Dissecting the complex interactions between leukemia cells and their milieu will be essential to develop new targeted therapies for HCL patients.